Copy Number Variation Mapping and Genomic Variation of Autochthonous and Commercial Turkey Populations - Strillacci, Maria G.; Gorla, Erica; Ríos-Utrera, Angel; Vega-Murillo, Vicente E.; Montaño-Bermudez, Moises; Garcia-Ruiz, Adriana; Cerolini, Silvia; Román-Ponce, Sergio I.; Bagnato, Alessandro (Frontiers in Genetics, 2019)
The evolution of the Mexican turkey population occurred independently for more than 500 years from other European ones and commercial hybrids. This study aims at investigating genomic diversity of several turkey populations using Copy Number Variants (CNV). A total of 116 individuals from 6 Italian breeds (Colle Euganei, Bronzato Comune Italiano, Parma e Piacenza, Brianzolo, Nero d’Italia and Ermellinato di Rovigo), 7 Narragansett, 38 commercial hybrids and 31 Mexican turkeys, were genotyped with the Affymetrix 600K SNP turkey array. The CNV calling was performed with the HMM of PennCNV software. CNV were summarized into CNV regions (CNVRs) at population level using BEDTools. Variability among populations has been addressed by hierarchical clustering (pvclust R package) and by principal component analysis (PCA). A total of 2,987 CNV were identified covering 4.65% of the autosomes of the Turkey_5.0/melGal5 assembly. The CNVRs including at least 2 individuals were 362, 189 gains, 116 losses and 57 complexes. Among these regions the 51% contain genes This study is the first CNV mapping of turkey population using 600K chip. CNVs clustered the individuals according to population and their geographical origin. CNVs are known to be indicators also of adaptation, as some researches in different species is suggesting. These results are likely reflecting the human action on domestication of wild turkey after its introduction into Europe and the directional selection occurring in the last 40 years to produce a fast-growing heavy bird.